Exploration of photoinitiators in ionic liquids - Rush, Joanna (My University, 2007)
Evaluates "the synthesis, utilization, and efficiency of photoinitiators in green solvents."
A poster containing visuals and text describing an undergraduate research project completed at the University of Wisconsin--Whitewater.
Keywords: Addition polymerization